Об аналитической интерпретации процессов в RL-, RC-цепях с учетом особого разложения входных прямоугольных импульсов - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
We give a solution of the problem on transient processes in RL- and RC-circuits under an input rectangular pulse voltage represented in the form of a special expansion.